Τρομακτικά τερατόμορφα ζώα της ελληνικής μυθολογίας, η απεικόνισή τους και ο συσχετισμός τους με κακόβουλα ζώα στα παιδικά παραμύθια - Παπαϊωάννου, Δαμιάνα (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2018)
Mythology is the reality that people create with their fantasy, so they can explain the unknown and the unexplained phenomena, that includes history and facts that happened in the past. Greek mythology is full with different creature and monsters, that they have an important role in the evolution of history, with the Olympic Gods and heroes. Some of these creatures were full of kindness and loyalty, with respect to the Gods, in contrast with some others that drew the terror and fear even to the Gods. These creatures were called the terrible monsters of Greek mythology, due to the fact that they spread the sense of terror and fear because of their actions and their appearance. Alongside, in children’s fairy tales a lot of bad and mean animals are mentioned, that they spread the terror and they cause the agitation to the heroes. The purpose of this research is to analyze the terrible monsters of Greek mythology with regard to their characteristics, their habits, their way of survival, what they symbolize and how they are depicted. The same time, this research its being done, for the bad and mean animals of children’s fairy tales, in order to find a correlation between these creatures. Specifically, through the research of different sources for this subject, characteristics for every different creature are analyzed, with a comparative method. Then, categorization is made through a table creation, so that a correlation between Greek’s mythology terrible monsters and bad animals, from children’s fairy tales, can be found. After analyzing the table, an additional study is being done, in order to find mοre clear and tactile result. Although, Greek mythology and children’s fairy tales are at a different chronological period, this research is about to find many interesting similarities between them.
Keywords: Greek mythology, horrible monsters, children’s fairy tales; ελληνική μυθολογία, τερατόμορφα ζώα, παιδικά παραμύθια